2015
DOI: 10.3109/09553002.2014.995382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole-body exposure to the 848.5 MHz code division multiple access (CDMA) electromagnetic field on adult neurogenesis in the young, healthy rat brain

Abstract: Our results suggest that exposure to the CDMA signal does not affect neurogenesis in the adult rat brain, at least under our experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This experiment was performed using a whole‐body RFID exposure system that has been previously described [Kim et al, ,; Kim et al, ]. Briefly, a whole‐body exposure system for animal experiments (IRETEC, Anyang, Korea) with 915 MHz RFID was developed using a reverberation chamber [Jung et al, ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This experiment was performed using a whole‐body RFID exposure system that has been previously described [Kim et al, ,; Kim et al, ]. Briefly, a whole‐body exposure system for animal experiments (IRETEC, Anyang, Korea) with 915 MHz RFID was developed using a reverberation chamber [Jung et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that exposure to 915 MHz RFID at a whole‐body specific absorption rate (SAR) of 4 W/kg had no statistically significant influence on the thyroid system [Kim et al, ] or on glucose metabolism [Kim et al, ]. Moreover, a code division multiple access (CDMA) signal at an SAR of 2 W/kg had no statistically significant influence on neurogenesis in adult rats [Kim et al, ]. Although RF‐EMFs were emitted in same or similar frequencies, if the modulation protocols for RF‐EMF were different, the biologic response could be different [Preece et al, ; Sukhotina et al, ; Kim et al, ,].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although that study was performed with a longer duration and stronger RF-EMF exposure than in the present study, no change was reported in neuronal cell fate. In our previous animal study with whole-body exposure to a 848.5-MHz CDMA signal at an SAR of 2 W/kg for 2 weeks, we observed no change in the numbers of BrdUpositive proliferating cells in the SVZ and DG [19]. Taken together with our previous report and the present study, although the experimental environments were different (local versus whole body, 1 day versus several weeks, and 915-MHz RFID versus 848.5-MHz CDMA), the RF-EMF exposure at an SAR of 2 W/kg had no harmful effects on neuronal cells in the adult rat brain.…”
Section: Resultsmentioning
confidence: 52%
“…A time delay in the process of neurite outgrowth may affect neurogenesis because neuronal activity is closely associated with the morphological maturation of neuronal cells [18]. According to our previous study with 848.5 MHz code division multiple access (CDMA) EMF, the differentiation of BrdU-positive cells in hippocampal DG and the SVZ were not affected after CDMA-EMF exposure at 2 W/kg SAR for 8 hours daily for 2 weeks in rats [19]. Previous studies could not demonstrate the influence of RF-EMFs on neurogenesis processes and on the fate of neuronal precursor cells in healthy adult rat brains.…”
Section: Effects Of 915 Mhz Radiofrequency Identification Electromagnmentioning
confidence: 96%